COMPARISON OF THE EFFICACY OF PLASMAPHERESIS AND INTRAVENOUS IMMUNOGLOBULIN IN INFLAMMATORY NEUROPATHIES: A LITERATURE REVIEW - Lena Jaworowicz,; Maria Wieczorek,; Weronika Plichtowicz-Kordowska,; Aleksandra Stępka,; Agnieszka Jóźwicka,; Karina Lewandowska,; Ewa Bąkowska,; Wojciech Janikowski, (International Journal of Innovative Technologies in Social Science, 2026)
Inflammatory neuropathies, including Guillain-Barré syndrome (GBS), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), and multifocal motor neuropathy (MMN) are immune-mediated disorders in which immunomodulatory therapy constitutes the cornerstone of treatment. Therapeutic plasma exchange (TPE) and intravenous immunoglobulin (IVIG) represent the two principal disease-modifying strategies. Although both modalities have demonstrated clinical efficacy, their mechanisms of action, safety profiles, durability of response, and logistical implications differ substantially.This review provides a structured comparative analysis of TPE and IVIG across major inflammatory neuropathies, synthesizing evidence from randomized controlled trials, meta-analyses, and international guidelines. In acute GBS, high-quality evidence supports broadly equivalent efficacy between TPE and IVIG in improving disability scores, reducing time to independent ambulation, and shortening mechanical ventilation duration. In CIDP, IVIG is strongly supported for both induction and maintenance therapy, whereas TPE is primarily used for short-term improvement or refractory disease. In MMN, IVIG remains the established first-line therapy, with plasma exchange demonstrating limited benefit.Safety considerations differ between modalities: IVIG is associated mainly with systemic infusion-related and thrombotic risks, whereas TPE carries procedural and vascular access-related complications. Logistical feasibility, infrastructure availability, cost structure, and global immunoglobulin supply constraints further influence therapeutic selection.Despite established efficacy, gaps remain regarding optimal sequencing strategies, long-term comparative outcomes, and biomarker-guided therapy selection. Future prospective and stratified studies are required to refine individualized treatment algorithms and optimize long-term patient outcomes in immune-mediated neuropathies.